Comparison of amorphous silicon absorber materials: Kinetics of light‐induced degradation. (6th November 2014) - Stuckelberger, Michael; Billet, Adrian; Riesen, Yannick; Boccard, Mathieu; Despeisse, Matthieu; Schüttauf, Jan‐Willem; Haug, Franz‐Josef; Ballif, Christophe
Abstract: We investigate the influence of the deposition parameters for intrinsic amorphous silicon absorber layers on light‐induced degradation (LID) of thin‐film silicon solar cells. The focus is on absorber layers with different bandgaps: on one side, solar cells with a wide‐bandgap absorber layer that provides open‐circuit voltages up to 1.04V; on the other, cells with short‐circuit current densities of 18.2mA/cm 2 with a 300‐nm‐thick narrow‐bandgap absorber layer, and 20mA/cm 2 at reverse bias for a cell with a 1000‐nm‐thick absorber layer. Between these extremes, we varied the hydrogen‐to‐silane ratio and the deposition pressure during the absorber layer deposition. The light‐induced degradation of these materials—covering the deposition regimes of low‐pressure, protocrystalline, polymorphous, and high‐pressure amorphous silicon—incorporated in single‐junction amorphous silicon solar cells is detailed here. For each pressure, we found an optimum hydrogen dilution with least LID close to the amorphous‐to‐microcrystalline transition. The relative LID is similar for all pressures at optimized hydrogen dilutions. Further, we present the influence of absorber layer thickness, p ‐layer thickness, and deposition rate on the kinetics of light‐induced degradation to facilitate the choice of a material for its application in several types of multi‐junction thin‐film silicon solar cells. We show that the degradation kinetics depends, in semi‐logarithmic scale, only weakly on time but more on deposition conditions. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : Which amorphous silicon absorber layer degrades least under light soaking? From wide‐bandgap material providing more than 1V open‐circuit voltage to narrow‐bandgap material providing up to 20mA/cm 2 current density in amorphous silicon single junction solar cells, we compare their light‐induced degradation kinetics and discuss applications. The varied deposition parameters include hydrogen‐to‐silane ratio, deposition pressure and temperature, excitation frequency and power, and p ‐ and i ‐layer thicknesses.